Computational fluid dynamics - Marin, Guy B. (Advances in chemical engineering, 2006)
The theme of the present volume is Computational Fluid Dynamics (CFD) and aims to show the state-of-the-art of the application of CFD in chemical engineering. The volume is made up of five complementary contributions, providing a style of between a tutorial and a research paper. Some contributions are entirely limited to velocity and temperature fields. Others emphasize the difficulties associated with the combination of transport and reaction. Contributions include dealing with the simulation of gas-liquid bubble columns and gas-liquid-solid fluidized beds. Addressing the different levels of modeling that are required in order to cover the full spectrum of length scales that are important for industrial applications. Stirred turbulent vessels and the chemical reactions. The importance of chemical reaction kinetics and the interaction with transport phenomena. Finally, looking at reactor engineering: the catalytic fixed bed reactor. * Original reviews * Leading chemical engineers as authors * Reviewing the state-of-the-art of Computational Fluid Dynamics (CFD).